1998
DOI: 10.1016/s0301-0082(97)00094-4
|View full text |Cite
|
Sign up to set email alerts
|

A structural basis for memory storage in mammals

Abstract: AbstractÐIt is proposed that altered dendrite length and de novo formation of new dendrite branches in cholinoceptive cells are responsible for long-term memory storage, a process enabled by the degradation of microtubule-associated protein-2. These memories are encoded as modality-speci®c associable representations. Accordingly, associable representations are con®ned to cytoarchitectonic modules of the cerebral cortex, hippocampus, and amygdala. The proposed sequence of events leading to long-term storage in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 168 publications
1
32
0
3
Order By: Relevance
“…Its function is also directly linked to its phosphorylation state, since phosphorylation of different domains leads to reduced tubulin binding (Brugg & Matus, 1991). MAP2 levels and conformation can be mediated by neurotransmitter systems (Halpain & Greengard, 1990;Diaz-Nido et al, 1993), whereby synaptic-mediated changes in the balance of kinases and phosphatases may alter MAP2 activity and, in turn, the microtubule network, allowing for synaptic plasticity (Avila et al, 1994;Woolf, 1998). Thus, a loss of MAP2 or an aberrant phosphorylation state may impair synaptic plasticity, as is noted in a murine model of HD (Usdin et al, 1999) and results in cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Its function is also directly linked to its phosphorylation state, since phosphorylation of different domains leads to reduced tubulin binding (Brugg & Matus, 1991). MAP2 levels and conformation can be mediated by neurotransmitter systems (Halpain & Greengard, 1990;Diaz-Nido et al, 1993), whereby synaptic-mediated changes in the balance of kinases and phosphatases may alter MAP2 activity and, in turn, the microtubule network, allowing for synaptic plasticity (Avila et al, 1994;Woolf, 1998). Thus, a loss of MAP2 or an aberrant phosphorylation state may impair synaptic plasticity, as is noted in a murine model of HD (Usdin et al, 1999) and results in cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, significant effects have been found when glutamatergic receptors were blocked before and after CTA acquisition in both the amygdala and IC (20 -22, 32, 33). The interaction of ACh and glutamate receptors is of special importance, considering that their activities may converge, as demonstrated by the study of the multiple signal-transduction pathways mediated by those receptors (34). Therefore, it has been demonstrated that one subunit of the NMDA receptor, the NR2B, undergoes phosphorylation by novel taste presentation or muscarinic activation (35).…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of temporal activity into the dendritic structure expands upon a data-based model that I proposed earlier whereby the microtubular structure is altered by reorganization of microtubule-associated protein-2 (MAP-2) in dendrite sets during the consolidation of memory (see Woolf, 1996Woolf, , 1997Woolf, , 1998. I have previously focused on the three-dimensional spatial organization of each altered dendrite set as a blueprint for conscious content (these dendrite sets are found throughout the neocortex, hippocampus, and amygdala).…”
Section: Possible Underlying Mechanisms In Dendritic Encodingmentioning
confidence: 97%
“…For the sake of comparison, the dendritic encoding model (or the snapshot model) presented here also implicates attentional processes in consciousness. Neuromodulatory systems, such as the cholinergic basal forebrain neurons, meter attention at the same time they induce conscious awareness of stimuli (for reviews, see Woolf, 1996Woolf, , 1997Woolf, , 1998. Moreover, the muscarinic receptor for acetylcholine takes about 500 ms to completely respond.…”
Section: The Time It Takes For Information To Reach Consciousnessmentioning
confidence: 99%